1998
DOI: 10.1074/jbc.273.20.12642
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycan Sulfation in Human Osteoarthritis

Abstract: Chondroitin lyase products of aggrecan and small proteoglycans from normal and osteoarthritic cartilages were analyzed for chain internal ⌬disaccharides and terminal mono-or disaccharides. Chondroitin and dermatan sulfate chains from arthritic cartilages were of essentially normal size and internal sulfation but had significantly altered sulfation of the terminal residues. Whereas in normal cartilage, ϳ60% of terminal GalNAc4S was 4,6-disulfated, it was reduced to ϳ30% in osteoarthritic cartilage. This is most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(82 citation statements)
references
References 37 publications
4
78
0
Order By: Relevance
“…It has also been shown that the finer structure of the GAG relating to the length of the GAG disaccharide chain and the degree of sulfation is important in the biomechanics of hydrated tissue (e.g. in cornea tissue [52] and osteoarthritic cartilage [53]). Our current DMB assay only measures total sulfated GAG content.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the finer structure of the GAG relating to the length of the GAG disaccharide chain and the degree of sulfation is important in the biomechanics of hydrated tissue (e.g. in cornea tissue [52] and osteoarthritic cartilage [53]). Our current DMB assay only measures total sulfated GAG content.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] As part of the aggrecan macromolecule, individual CS-GAGs have the tendency to assume an extended, rodlike conformation rather than a random coil under normal physiological conditions of 0.15 M salt concentration due to intramolecular electrostatic repulsion between neighboring negatively charged carboxylate and sulfate groups (i.e., intercharge distance ) 0.64 nm), 3 as well as the high chain packing density.…”
Section: Introductionmentioning
confidence: 99%
“…1 Parenthetical numbers refer to the sulfated glycopeptides described in Table 4. 2 Mass accuracy compromised due to isobaric interference. 3 Nonsulfated glycopeptides were identified previously in reference [16].…”
Section: Comparision To (ϫ)Esi-msmentioning
confidence: 99%
“…It is an integral, ubiquitous component of the polymeric glycosaminoglycans, present in the extra-cellular matrix [1]. Changes in glycosaminoglycan sulfation have been linked to arthritis and other disease states [2][3][4]. Sulfation also is prevalent on cell-surface oligosaccharides in virtually all mammalian tissues, and its presence is fundamental in cellular communication events [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation